Biphenyl-4-carbaldehyde azine - Ariffin, Azhar; Ng, S.W.; Yehye, W.A; Rahman, N.A. (International Union of Crystallography, 2008)
The complete molecule of the title compound, C(26)H(20)N(2), is generated by crystallographic inversion symmetry. The terminal phenyl ring is twisted by 19.2 (1)degrees with respect to the adjacent phenylene ring.